2021
DOI: 10.1093/gerona/glab370
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Ambient Fine Particulate Matter and Physical Functioning in Middle-Aged and Older Chinese Adults: A Nationwide Longitudinal Study

Abstract: Background Exposure to air pollution is associated with several chronic diseases and subclinical processes that could subsequently contribute to physical disability. However, whether and to what extent air pollution exposure is associated with objective measures of physical functioning remains understudied. Methods We used longitudinal data from the China Health and Retirement Longitudinal Study (CHARLS) and included 10,823 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Recent studies have shown that environmental pollutants such as PM2.5 are also risk factors for falls and fall-related injuries [31]. Short-term and long-term exposure to environmental pollutants may be associated with a series of adverse health outcomes of physical function, such as slower gait, balance disorders, and tremors [14,21]. Moreover, some studies have shown the relationships between the indoor use of solid fuels and respiratory diseases, cardiovascular diseases, and cognitive dysfunction in different regions [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown that environmental pollutants such as PM2.5 are also risk factors for falls and fall-related injuries [31]. Short-term and long-term exposure to environmental pollutants may be associated with a series of adverse health outcomes of physical function, such as slower gait, balance disorders, and tremors [14,21]. Moreover, some studies have shown the relationships between the indoor use of solid fuels and respiratory diseases, cardiovascular diseases, and cognitive dysfunction in different regions [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies supported that people with diabetes were at a significantly higher risk of falls and injurious falls than people without diabetes across [42]. Huiyu Wang et al found that each 10 μg/m3 increase in annual averaged concentrations of PM2.5 was associated with a 5% risk of reduced balance ability [21]. In addition, some experiments have demonstrated the adverse effects of solid fuels or indoor air pollution on physical health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From 2013 to 2020, a 48% decrease in PM 2.5 concentration was associated with a 21% reduction in attributable deaths (1.75 [95% confidence interval 1.64–1.85] million in 2013 to 1.39 [95% confidence interval 1.27–1.51] million in 2020) [ 3 ]. CAAs were associated with improvements in multiple health indicators, including lung function [ 6 ], lung-cancer incidence [ 7 ] and survival rate [ 8 ], kidney function [ 9 ], blood lipids [ 10 ], physical functions [ 11 ], household medical expenditure [ 12 ], and mental health [ 13–15 ]. However, increases in O 3 concentrations, particularly during the first stage, increased mortality in populous eastern China [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study contributes to the literature by newly evaluating associations between long-term exposure to air pollution and help for health or memory problems at older ages, which may be associated with physical or cognitive functional losses due to air pollution's impacts on chronic disease development. Although related work has investigated associations with self-reported difficulties in ADL 12,35,36 and performance-based tests 14,[37][38][39] alone, to our knowledge, our outcome is novel in its capture of more severe dysfunction that requires personal care for ADL and IADL. This may make this research more directly informative of the economic burdens associated with air pollution in older adults.…”
mentioning
confidence: 99%